Olfactory Impairment Among Rural-Dwelling Chinese Older Adults: Prevalence and Associations With Demographic, Lifestyle, and Clinical Factors - Dong, Yi; Wang, Yongxiang; Liu, Keke; Liu, Rui; Tang, Shi; Zhang, Qinghua; Ekström, Ingrid; Laukka, Erika J.; Du, Yifeng; Qiu, Chengxuan (Frontiers in Aging Neuroscience, 2021)
Objective Olfactory impairment (OI) refers to decreased (hyposmia) or absent (anosmia) ability to smell. We sought to estimate the prevalence and correlates of OI among rural-dwelling Chinese older adults. Methods This population-based cross-sectional analysis included 4514 participants (age ≥65 years; 56.7% women) from the Multidomain Interventions to Delay Dementia and Disability in Rural China. The 16-item Sniffin’ Sticks identification test (SSIT) was used to assess olfactory function. OI was defined as the SSIT score ≤10, hyposmia as SSIT score of 8-10, and anosmia as SSIT score <8. Multivariable logistic regression models were used to examine factors associated with OI. Results The overall prevalence was 67.7% for OI, 35.3% for hyposmia, and 32.5% for anosmia. The prevalence increased with age for OI and anosmia, but not for hyposmia. The multivariable-adjusted odds ratio (OR) of OI was 2.10 (95% CI 1.69-2.61) for illiteracy and 1.41 (1.18-1.70) for elementary school (vs. middle school or above), 1.30 (1.01-1.67) for current smoking (vs. never smoking), 0.86 (0.74-0.99) for overweight and 0.73 (0.61-0.87) for obesity (vs. normal weight), 4.21 (2.23-7.94) for dementia, 1.68 (1.23-2.30) for head injury, and 1.44 (1.14-1.83) for sinonasal disease. Illiteracy in combination with either male sex or diabetes was significantly associated with an over two-fold increased OR of OI (p for interactions<.05). Conclusion OI is highly prevalent that affects over two-thirds of rural-dwelling older adults in China. OI is correlated with illiteracy, current smoking, dementia, head injury, and sinonasal disease, but negatively associated with overweight or obesity. OI as a potential clinical marker of neurodegenerative disorders among older adults deserves further investigation.